A Preoperative Scoring System to Predict the Risk of Inadequate Lymph Node Count in Rectal Cancer - Zhang, Hao; Wang, Chunlin; Liu, Yunxiao; Hu, Hanqing; Wang, Guiyu (Frontiers in Oncology, 2022)
Purpose The aim of this study was to develop and validate a preoperative scoring system to stratify rectal cancer (RC) patients with different risks of inadequate lymph node examination. Methods A total of 1,375 stage I–III RC patients between 2011 and 2020 from the Second Affiliated Hospital of Harbin Medical University were included in the retrospective study and randomly divided into a development set (n = 688) and a validation set (n = 687). The logistic regression model was used to determine independent factors contributing to lymph node count (LNC) < 12. A preoperative scoring system was constructed based on beta (β) coefficients. The area under the receiver operating curve (AUC) was used to test model discrimination. Results Preoperative significant indicators related to LNC < 12 included age, tumor size, tumor location, and CEA. The AUCs of the scoring system for development and validation sets were 0.694 (95% CI = 0.648–0.741) and 0.666 (95% CI = 0.615–0.716), respectively. Patients who scored 0–2, 3–4, and 5–6 were classified into the low-risk group, medium-risk group, and high-risk group, respectively. Conclusions The preoperative scoring system could identify RC patients with high risk of inadequate lymphadenectomy accurately and further provide a reference to perform preoperative lymph node staining in targeted patients to reduce the difficulty of meeting the 12-node standard, with the purpose of accurate tumor stage and favorable prognosis.